Influences of specific surfactant structures on biohydrogen production from oily wastewater in batch and continuous anaerobic dark fermentation. (September 2022) - Ahmar Siddiqui, Muhammad; Parnthong, Jatuporn; Kungsanant, Suratsawadee; Chavadej, Sumaeth; Chaiprapat, Sumate
Graphical abstract: Highlights: Nonionic surfactants improve oil solubilization by micelles formation in POME. Dosing surfactant at critical micelle concentration optimally enhanced H2 yield. Surfactant comparison was based on efficiency for H2 yield and cost of application. Oil degradation in an anaerobic digester leaped to 59% with Tergitol 15-S-9. H2 yield improved 32% when suppling Tergitol 15-S-9 to POME in continuous digestion. Abstract: Residual oil in palm oil mill effluent (POME) poses difficulties in its treatment chain. Non-ionic surfactants containing different hydrophobic tail structures and their optimal concentrations were evaluated for effectiveness in biohydrogen production. By adding the surfactants at their critical micelle concentration in synthetic oily wastewater, the maximal H2 yield was increased by 2.2 and 3.5 times for Triton X-100 and Tergitol 15-S-9, respectively, compared to the control. Using real POME, the supplemental Tergitol 15-S-9 resulted in a 56.4 % improvement in H2 production. For continuous digestion studies, pure POME and Tergitol 15-S-9 supplemented POME (sPOME) were fed to thermophilic anaerobic sequencing batch reactors (ASBRs) under hydraulic retention time (HRT) of 32–12.5 days. Optimally at HRT 19 days, H2 content in the biogas from sPOME-fed ASBR was noticeably higher, which gave a superior yield of 203.4 mLH2 /gCODremoved (+15 %).